EFISIENSI PUPUK FOSFOR PADA BEBERAPA KULTIVAR KEDELAI (GLYCINE MAX L. MERRIL) - Rosmimi '; Idwar '; Muhammad Syafril (Jurnal Sagu, 2002)
Very low level of Phosphorus (P) availability in lowland area may cause serious hidrance on soybeanproduction in Riau. Addition of P fertilizer to the soil is significant for accelerating soybean production,however there were very limited farmers which were wiling to fertilize their soybean due to limitedcapital and unavailable cultivars that is efficient in absorbing P from soil particles. Therefore, it isimportant to investigate the efficiency of P fertilizer by soybean cultivars (Glycine nuv: L . Merril).This experiment are intended to identify soybean cultivars that are responsive to P-Fertilizer from dieobservation on the growth and production of soybean and to investigate the efficiency of P-Fertilizerby soybean cultivars. The experiment has been conducted in the Field Station of Faculty of Agricul-ture, Riau University located at Pekanbaru, Riau. The materials consisting of 5 cultivars of soybean, is: Kipas Putih, Malabar, Willis, Argoimtlyo and Bromo. Had been planted in plots applied by fourlevels of P fertilizer. The levels of P fertilizer were 20 kg, 40 kg, 60 kg PO per hectare and control.The experiment were arranged in a randomized factorial block experiment with three replications. Ingeneral, addition of fertillizcrdid not influence crop growth significantly especially on vegetative diyweight, the percentage of filled pods, individual seed weight, and P absorption efficiency.The cultivarsdiffered significantly in response to P fertilizer aplication. Optimum efficiency of seed production wasfound for Kipas Putih and Bromo at the level of 40 Kg PO per hectare while in other cultivars, theoptimal, was reached when they where not fertilized by P fertilizer. Optimum absorption of P fertilizerwere detected on Kipas Putih and Bromo at the level of 40 kg PO, per hectare, while in othercultivars the optimum absorption efficiency was obtained when crops were not fertilized.